Maximum Security, Fourth Edition - Anonymous (Que, 2002)
Maximum Security, Fourth Edition provides updated, comprehensive, platform-by-platform coverage of security issues, and includes clear, to the point descriptions of the most common techniques hackers use to penetrate systems. This book provides information for security administrators and others interested in computer and network security and provides them with techniques to take steps to protect their systems.